Photodynamic activity of hematoporphyrin conjugates with gold nanoparticles: experiments in vitro - Gamaleia, N.F.; Shishko, E.D.; Dolinsky, G.A.; Shcherbakov, A.B.; Usatenko, A.V.; Kholin, V.V. (Experimental Oncology, 2010)
Aim: To synthesize a conjugate of hematoporphyrin with gold nanoparticles, and to evaluate its photodynamic activity in experiments on cultures of transformed cells. Methods: nanosized gold particles and nanocomposites synthesis methods, cell culture methods, photobiology methods, trypan blue dye exclusion test, chemiluminescence assay. Results: Various hematoporphyrin-gold nanocomposites were obtained, which contained similar hematoporphyrin concentration (5 μg/ml) and varied concentrations (0.5–5 μg/ml) of gold nanoparticles with a diameter of 15 nm or 45 nm. It was established by chemiluminescence method that nanocomposites synthesized induce more efficiently the formation of photo-oxidative products than original photosensitizer. The experiments with transformed cell lines showed that photodynamic in vitro activity of synthesized hematoporphyrin-nanogold composites is much higher than that of the original photosensitizer. The better activity of the nanocomposites with gold particles of 45 nm vs such of 15 nm which was demonstrated in the experiments, can be apparently connected with the fact that bigger particles are able to transport more porphyrin molecules into malignant cells. Conclusion: The results obtained warrant the necessity of further studies with hematoporphyrin-gold nanocomposites in vivo on transplanted tumors of animals which have to define the real perspectives of the nanocomposites application in PDT.